Analysis of the National Program for Strengthening Family Farming (PRONAF) "More Food" in Brazilian regions from 2013 to 2022 (Research, Society and Development, 2023)
The objective of the study was to evaluate the effectiveness of the National Program for Strengthening Family Farming (PRONAF) "More Food" in achieving its goals, such as increasing the income of farming families and diversifying agricultural production, as well as getting a better understanding of the reality of farming families and adapting the program to their needs. The methodology used was a descriptive approach to study the collected data, organizing and highlighting the most important characteristics of a series of observations. Various types of graphs were used, as well as synthetic measures such as percentages, indices, and averages. The research is also classified as bibliographic, using information and data already published and made available by the government itself on the internet. The results showed a significant increase in the volume of contracts and resources for the Pronaf Mais Alimentos program over the years analyzed. Additionally, it was possible to verify that the program has contributed to increasing the income of farming families and diversifying agricultural production in different regions of Brazil. Based on the results obtained, it is concluded that Pronaf Mais Alimentos has been effective in achieving its objectives of promoting the economic and social development of farming families in Brazil. However, it is important to continue evaluating its effectiveness over time and adapting it to the needs of farming families to ensure its ongoing success.